New Aspects on the IL Khans International Conference in Ulaan Baatar, Mongolia, 21–23 May 2014 - Judith Kolbas (Золотоордынское обозрение)
A special conference held in Ulaan Baatar, Mongolia, explored new aspects on the Il Khans. It was jointly sponsored by the Mongolian National University and the University of Indiana, Bloomington, USA, from 21 to 23 May of 2014. Twenty-one invited speakers presented topics in various panels that each had a unifying theme. The entire event was extremely well organized by Dashdondog Bayarsaihkan (Ph.D. from the University of Oxford) on the faculty of the History Department of the Mongolian National University. There was, indeed, much new information on imperial Mongol activity in Greater Iran, and the proceedings will be published in Mongolia and abroad. Several important trends in current research on the Mongols in Iran became strikingly apparent during the conference. The first was that the standard texts that have been relied upon for so long, such as Rashid al-Din, Juvayni and Wassaf, need much more critical analysis than has occurred before. These works sometimes disagree with other material from more local or overlooked sources such as from the Nestorian community in Irbil, the Armenian hagiographies, the position of Anatolia and Afghanistan within the Il Khanate and finally diplomatic correspondence. The second development is that all the sources can fruitfully be analyzed more carefully from reviewing Rashid al-Din’s records to al-Qalqashandi’s terminology. Thirdly, although the period is richer in sources than almost any other previous era, even more material is available than has been normally considered. With this significant increase of source material, critiques of the previously common references and analyses of forces below the military and court levels, this conference exhibited the vibrant expansion of Il Khanid studies in its own right, so long an adjunct to regional studies of other states.